Platelet Lysate Inhibits NF-κB Activation and Induces Proliferation and an Alert State in Quiescent Human Umbilical Vein Endothelial Cells Retaining Their Differentiation Capability - Romaldini, Alessio (Cells, 2019)
Injured blood vessel repair and blood circulation re-establishment are crucial events for tissue repair. We investigated in primary cultures of human umbilical vein endothelial cells (HUVEC), the effects of platelet lysate (PL), a cocktail of factors released by activated platelets following blood vessel disruption and involved in the wound-healing process triggering. PL exerted a protective effect on HUVEC in an inflammatory milieu by inhibiting IL-1α-activated NF-κB pathway and by inducing the secretion of PGE(2), a pro-resolving molecule in the wound microenvironment. Moreover, PL enhanced HUVEC proliferation, without affecting their capability of forming tube-like structures on matrigel, and activated resting quiescent cells to re-enter cell cycle. In agreement with these findings, proliferation-related pathways Akt and ERK(1/2) were activated. The expression of the cell-cycle activator Cyclin D1 was also enhanced, as well as the expression of the High Mobility Group Box-1 (HMGB1), a protein of the alarmin group involved in tissue homeostasis, repair, and remodeling. These in vitro data suggest a possible in vivo contribution of PL to new vessel formation after a wound by activation of cells resident in vessel walls. Our biochemical study provides a rationale for the clinical use of PL in the treatment of wound healing-related pathologies.